In vitro Clot Lysis Activity of Phenolic Compound Degrading Product From Lignin Sugarcane Baggase Using Ochrobactrum sp. - Arie Srihardyastuti; Moh Farid Rahman; Tri Ardyati; Anna Roosdiana; Indah Prihartini (The Journal of Pure and Applied Chemistry Research, 2020)
Sugarcane bagasse (Saccharum officinarum L) is a readily available waste product of cane sugar processing. The content of lignocelluloses in sugarcane bagasse is approximately 52.7% cellulose, 20% hemicelluloses, and 24.2% lignin. Lignin can be degraded enzymatically by using microorganisms, such as Ochrobactrum sp. Monomer derived from lignin degradation using these bacteria in the optimum condition of sugarcane fermentation (pH 6, temperature 40 °C, for 5 days of incubation, the concentrations of starter 29%) by GC-MS yielded phenolic compounds such as 4-methyl-2, 6-di-tert-butylphenol; 2,6-di-tert-butylquinone; phenol, and p-hydroxybenzaldehide. The thrombolytic activity of these lignin monomers can be tested in-vitro by measuring the ability of clot lysis. Lignin did not have in-vitro clot lysis activity, whereas the lignin monomers in filtrat of fermented sugarcane bagasse have an in-vitro clot lysis activity, although its capacity is not as high as streptokinase.